Full-Length Transcriptomics Reveals Complex Molecular Mechanism of Salt Tolerance in Bromus inermis L. - Li, Qian; Song, Jiaxing; Zhou, Yi; Chen, Yingxia; Zhang, Lei; Pang, Yongzhen; Zhang, Bo (Frontiers in Plant Science, 2022)
Bromus inermis L. (commonly known as smooth bromegrass) is a grass species with high nutritional value, great palatability, cold-tolerance and grazing-resistance, which has been widely cultivated for pasture and sand fixation in northern and northwestern China. Salt stress is a main environmental factor limiting growth and production of smooth bromegrass. In this study, we performed PacBio Iso-Seq to construct the first full-length transcriptome database for smooth bromegrass under continuous NaCl treatmens. Third-generation full-length transcript sequencing yielded 19.67 G Polymerase Read Bases, which were assembled into 355,836 full-length transcripts with an average length of 2542 bp. A total of 116,578 differentially expressed genes were revealed by comparing the results of third-generation sequencing and second-generation sequencing. GO and KEGG enrichment analyses revealed that multiple pathways were differently activated in leaves or roots under NaCl treatment at different time points. In particular, a number of genes participate in molecular network of plant signal perception, signal transduction, transcription regulation, antioxidant defense, and ion regulation were affected by NaCl treatment. In particular, the CBL-CIPK, MAPK, ABA signaling network and SOS core regulatory pathways of Ca2+ signal transduction were activated to regulate salt stress response. In addition, the expression patterns of 10 salt-responsive genes were validated by quantitative real-time PCR, which were consistent with the changes in transcript abundance detected by RNA-Seq. Our results reveal the molecular regulation of smooth bromegrass in response to salt stress, which are important for further investigation of critical salt responsive genes and molecular breeding of salt-tolerant smooth bromegrass.